Chemical composition and color analysis of BRSMG Caravera rice in relation to urea sources and dosages - Gisele Souza Fernandes; Luan Alberto Andrade; Luíza Aparecida Carneiro Fernandes; Joelma Pereira (Revista Tecnológica, 2024)
Rice is an essential food for the diet of the Brazilian population. Parboiling and nitrogen fertilization are processes which aim to improve the physical-chemical composition of these grains. The objective of this study was to evaluate the chemical composition as well as the color of unparboiled and parboiled rice fertilized with policote and kimcoat urea in dosages of 40, 80, and 120 ha-1. When it comes to the chemical composition, the parboiled rice presented higher levels of moisture, ash, and crude fiber. It also presented low lipid levels, non-nitrogenized extract, and color difference. The nitrogen fertilization strongly impacted the protein levels of rice. It was found that the fertilization with policote and kimcoat urea might have a stronger impact on the protein levels of rice, and that the parboiling process impact further aspects of the chemical composition and color of rice.